Expression of RSK4, CD44 and MMP-9 is upregulated and positively correlated in metastatic ccRCC - Jing Ma; Mingyang Li; Jia Chai; Kaijing Wang; Peifeng Li; Yixiong Liu; Danhui Zhao; Junpeng Xu; Kangjie Yu; Qingguo Yan; Shuangping Guo; Zhe Wang; et al. (BMC, 2020)
Abstract Background To investigate the expression and function of RSK4, MMP-9 and CD44 in primary clear cell renal cell carcinoma (primary ccRCC) and metastatic clear cell renal cell carcinoma (metastatic ccRCC), as well as the correlation with clinicopathological features of patients. Method The expression levels of RSK4, CD44 and MMP-9 in 52 primary ccRCC samples and 48 metastatic ccRCC samples were detected by immunohistochemistry, and the relationship between RSK4, CD44 and MMP-9 expression and clinicopathological features as well as prognosis of metastatic ccRCC patients was statistically analysed. Ectopic RSK4 expression in ccRCC cell lines was performed to determine its effect on cell cycle regulation, tumour invasiveness, and metastatic capability. Results The positive rates of RSK4, MMP-9 and CD44 expression in metastatic ccRCC tissues were 75, 68.75 and 91.7%, respectively, while the rates in primary ccRCC tissues were 44.2, 34.6 and 69.2%, respectively. Thus, the positive rates in metastatic ccRCC were higher than those in primary ccRCC (P RSK4 = 0. 002; P MMP-9 = 0. 002; P CD44 = 0. 001). However, the expression of RSK4, CD44 and MMP-9 was unrelated to age, gender, or metastatic sites (P > 0.05) but was related to WHO/ISUP nucleolar grade (P RSK4 = 0.019; P CD44 = 0.026; P MMP-9 = 0.049). In metastatic ccRCC, expression among the three proteins showed a positive correlation (P = 0.008). Moreover, expression between RSK4 and CD44 (P = 0.019) and MMP-9 and CD44 (P = 0.05) also showed positive correlations, whereas RSK4 and MMP-9 showed no significant correlation (P = 1.00). Molecular studies showed that overexpression of RSK4 could enhance the invasive and migratory abilities of ccRCC cell lines through the regulation of CD44 and MMP-9 expression and vice versa. Conclusions The overexpression of RSK4, MMP-9 and CD44 is associated with the invasion and metastasis of ccRCC, indicating that they could be potential prognostic factors and serve as new potential therapeutic targets for ccRCC.